Speech by Dr. Margaret Gikuhi Chairperson, University of Embu Council During The 4th Graduation Ceremony - Gikuhi, Margaret (University of Embu, 2019)
Speech by Dr. Margaret Gikuhi Chairperson, University of Embu Council During The 4th Graduation Ceremony Held at The University Of Embu on Friday 20th September, 2019